Closed loop supply chain network with LCC - Hasanov, Elkhan; Hasanov, Parviz; Babayev, Yadullah (Journal of Management, Economics, and Industrial Organization, 2018)
Economic growth increases production and result of this increased consumption and waste. Considering the amount of waste generated every year the managing of waste is quickly becoming a tremendous problem for the environment. Thus manufacturers and the general public have come to recognize the importance of waste management. The aim of the paper is to revisit an EOQ type reverse logistics model Ritcher (1996a,b) and highlights the potential benefits of developing recycle methodology in the manufacture and remanufacture. Figures and mathematical models are developed and results investigated with examples. The developed model was compared with the model of Ritcher (1996a,b) to stress the importance of waste management.
Keywords: Supply Chain; Logistics; Recycle Methodology